THE EFFECT OF WORD FORMATION STRATEGY ON GRADE SEVEN STUDENTS’ VOCABULARY LEARNING RESULT AT SMPN 20 BEKASI - Deddy Suezdi (Lingua, 2017)
This study was to investigate whether or not significant effect of the word formation strategy on grade seven students’ vocabulary learning result at SMPN 20 Bekasi. The sampling technique which used in this research is cluster random sampling, with the total samples is 81 students. The samples consists of 41 students of experimental class and 40 students of control class. The research methodology adopted was quasi experimental method, with the research design used post-test only control group design. The instrument used in this research in an objective test given to the students. The research data were analyzed descriptively and inferentially. To indicated significant effect of learning vocabulary through word formation strategy on vocabulary learning result of SMPN 20 Bekasi students, a post-test was used. The results was rejected null hypothesis, It means that learning vocabulary through word formation strategy positively affected SMPN 20 Bekasi students’ vocabulary learning result.